Pathogenesis and potential relative risk factors of diabetic neuropathic osteoarthropathy - Hong-Mou Zhao; Jia-Yu Diao; Xiao-Jun Liang; Feng Zhang; Ding-Jun Hao (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Diabetic neuropathic osteoarthropathy (DNOAP) is an uncommon, but with considerable morbidity and mortality rates, complication of diabetes. The real pathogenesis is still unclear. The two popular theories are the neuro-vascular theory and neuro-traumatic theory. Most theories and pathways focused on the uncontrolled inflammations that resulted in the final common pathway, receptor activator of nuclear factor κβ ligand (RANKL)/osteoprotegerin (OPG) axis, for the decreased bone density in DNOAP with an osteoclast and osteoblast imbalance. However, the RANKL/OPG pathway does not explain all the changes, other pathways and factors also play roles. A lot of DNOAP potential relative risk factors were evaluated and reported in the literature, including age, gender, weight, duration and type of diabetes, bone mineral density, peripheral neuropathy and arterial disease, trauma history, and some others. However, most of them are still in debates. Future studies focus on the pathogenesis of DNOAP are still needed, especially for the genetic factors. And, the relationship between DNOAP and those potential relative risk factors are still need to further clarify.